A density functional study of the coronene-pyrrole system in relation to its possible application as NO2 and NH3 sensors - Olmedo-Martinez, Cinthya Susana; Hernandez-Duarte, Jesus Moises; Mejia-Olvera, Roberto; Pacheco-Ortin, Sandy Maria; Agacino-Valdes, Esther (European Journal of Chemistry, 2022)
According to recent research on the application of graphene materials as sensors and particularly polypyrrole-graphene materials, which are especially promising, the functionalization of graphene with a pyrrole molecule might be considered a viable alternative as a NO2 and NH3 sensor. In this way, a graphene sheet simulated as a coronene molecule was used in order to test whether this kind of functionalization could be useful for detecting the NO2 and NH3 toxic gases with a relatively high sensitivity. NO2 was studied as an example of an electron acceptor molecule, and NH3 as an electron donor molecule. Both molecules were adsorbed on two different regions of the functionalized adsorbent, and the energy ranges found for adsorption were reported and compared with those of the pristine graphene. The results indicated that in the coronene-pyrrole system, pyrrole tends to lie almost parallel to the coronene sheet in a π-π stacking interaction between the two conjugated systems, being the closest distances of 3.0 and 3.2 Å. The use of Δ (ΔHOMO-LUMO) as a descriptor confirmed that the coronene-pyrrole system is a good option as a NO2- and NH3-sensor; therefore, it might be an easy and suitable descriptor for characterizing the performance of a sensor; all calculations were made using a Density Functional formalism, through a functional M06-2X in combination with the 6-31G(d,p) basis set.